Correlation of Insulin Resistance Indexes with Blood levels of Zonulin, clusterin in patients with Nonalcoholic Fatty Liver Disease - Hamad, Marwan Habeeb; Sarhat, Entedhar Rifaat (Journal of Neonatal Surgery, 2025)
Background: Nonalcoholic fatty liver disease (NAFLD) is a prevalent metabolic disorder affecting approximately 25% of the global population. It is closely linked to insulin resistance (IR), obesity, type 2 diabetes, and metabolic syndrome. Objectives: The of this study to analyze the correlation between insulin resistance indexes (HOMA-IR, TyG Index) and serum levels of zonulin and clusterin in patients with NAFLD. Method and materials: A case-control study was conducted at Kirkuk Teaching Hospital in Iraq. The study took place from September 15, 2024, to January 18, 2025, and included 90 participants between 30 and 60 years of age─60 patients diagnosed with NAFLD (30 males and 30 females) and 30 healthy controls (15 males and 15 females). Serum measurements of fasting blood glucose (FBS) and triglycerides (TG) were performed using automated biochemical analyzers. Fasting insulin, zonulin, and clusterin were estimated by enzyme-linked immunosorbent assay (ELISA). Results: NAFLD patients exhibited significantly higher fasting blood sugar (132.94 ± 21.34 mg/dL vs. 100.19 ± 10.61 mg/dL, p<0.01), triglycerides (191.19 ± 19.04 mg/dL vs. 144.53 ± 16.48 mg/dL, p<0.01), insulin (19.98 ± 4.54 mIU/mL vs. 8.97 ± 3.47 mIU/mL, p<0.01), HOMA-IR (6.73 ± 2.44 vs. 2.27 ± 1.03, p<0.01), and TyG Index (9.43 ± 0.23 vs. 8.88 ± 0.20, p<0.01) than controls. Zonulin (72.50 ± 8.24 ng/mL vs. 57.17 ± 8.26 ng/mL, p<0.01) and clusterin (186.82 ± 25.29 ng/mL vs. 132.79 ± 21.76 ng/mL, p<0.01) were also significantly elevated. Correlation analysis showed zonulin and clusterin were positively associated with insulin resistance markers (HOMA-IR, fasting insulin and TyG Index; p<0.01). ROC curve analysis revealed HOMA-IR (AUC = 0.975) as the most powerful diagnostic marker, followed by TyG Index (AUC = 0.966), clusterin (AUC = 0.945), and zonulin (AUC = 0.903). Conclusions: Zonulin, and clusterin levels were significantly higher in patients with NAFLD, HOMA-IR remains the best predictor of NAFLD, while TyG Index, clusterin, and zonulin may serve as additional biomarkers.